Identification of distinct bio-signatures in whole blood and in-tube quantiferon pellets of Tuberculosis (TB) close contacts (CCs) and TB patients with and without type 2 diabetes (T2D) - Tshivhula, Happy (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.